Trends in Differences in US Mortality Rates Between Black and White Infants - Riddell, Corinne A. (JAMA Pediatr, 2017)
This study investigates recent trends in the absolute difference in overall and cause-specific infant mortality rates between non-Hispanic black infants and white infants.